Transcriptome Sequencing of Listeria monocytogenes Reveals Major Gene Expression Changes in Response to Lactic Acid Stress Exposure but a Less Pronounced Response to Oxidative Stress - Cortes, Bienvenido W.; Naditz, Annabel L.; Anast, Justin M.; Schmitz-Esser, Stephan (Frontiers in Microbiology, 2020)
Listeria (L.) monocytogenes is a well-characterized pathogen that represents a major threat to food safety. In this study, we examine the chromosomal and plasmid transcriptomes of two different L. monocytogenes strains, 6179 (belonging to sequence type (ST) 121) and R479a (ST8), in response to 30 minute exposure to oxidative (0.01% hydrogen peroxide) and acid (1% lactic acid, pH 3.4) stress. The exposure to oxidative stress resulted in 102 and 9 differentially expressed (DE) genes in the chromosomal transcriptomes of 6179 and R479a, respectively. In contrast, 2280 and 2151 DE genes were observed in the respective chromosomal transcriptomes of 6179 and R479a in response to lactic acid stress. During lactic acid stress, we observed upregulation of numerous genes known to be involved in the L. monocytogenes stress response, including multiple members of the σB regulon, many of which have not been functionally characterized. Among these genes, homologs of lmo2230 were highly upregulated in both strains. Most notably, the σB-dependent non-coding RNA Rli47 was by far the most highly expressed gene in both 6179 and R479a, accounting for an average of 28% and 38% of all mapped reads in the respective chromosomal transcriptomes. In response to oxidative stress, one DE gene was identified in the 6179 plasmid transcriptome, and no DE genes were observed in the transcriptome of the R479a plasmid. However, lactic acid exposure resulted in upregulation of the stress response gene clpL, among others, on the 6179 plasmid. In R479a, a number of uncharacterized plasmid genes were upregulated, indicating a potential role in stress response. Furthermore, an average of 65% of all mapped transcriptome reads for the R479a plasmid following acid stress were mapped to an intergenic region bearing similarity to riboswitches involved in transition metal resistance. The results of this study support the conclusion that members of the σB regulon, particularly lmo2230 and the non-coding RNA Rli47, play an integral role in the response of L. monocytogenes to acid stress. Furthermore, we report the first global transcriptome sequencing analysis of L. monocytogenes plasmid gene expression and identify a putative, plasmid-encoded riboswitch with potential involvement in response to acid exposure.